Criminal Liability for Abuse of Hard Drugs for Illegal Abortion Practices - Nathania, Jovita; Sutarno, Sutarno`; Adriano, Adriano; Zamroni, Zamroni (Dinasti Research, 2025)
In Indonesia, abortion is still a major and contentious legal and health issue, especially when it is carried out beyond the bounds of the law. Illegal abortion practices have increased as a result of the growing number of unintended pregnancies, which are mostly caused by premarital sex, a lack of information, and adolescent-free association. Criminal culpability for persons, including women who knowingly have abortions and others who help or facilitate the procedure, is the focus of this article. This paper analyzes statutory rules, court rulings, and legal principles using a normative legal research approach, with a special emphasis on Decision No. 1977/Pid.Sus/2019/PN.Sby. The results show that under Articles 20 and 21 of the Criminal Code and Article 194 of the Health Law, the lady who conducted the abortion as well as those who supplied the means, money, or instructions are criminally culpable. The case illustrates how accomplices are also subject to legal culpability in addition to the principal perpetrator. It emphasizes the value of education and regulation in preventing the abuse of abortion-inducing medications and reaffirms the significance of legal clarity in abortion situations. To address the risks of unsafe, illegal abortions in Indonesia, this research advances health law and advocates for stronger legal enforcement as well as more public awareness